Conceptual Design TanyaAja Startups Connect with Experts Instantly Using the Sprint Method - Muhammad Iqbal; Meidick Dias Devasela; Tata Sutabri (Jurnal Info Sains : Informatika dan Sains, 2023)
Conceptual Design of TanyaAja Startup to Instantly Connect with Experts Using Sprint Method discusses an innovative concept that can help individuals connect with experts in various fields easily and quickly through mobile applications. This concept is based on the application of the Sprint method in prototyping the TanyaAja application, which includes the stages of understanding, determining focus, generating ideas, prototyping, and validating. This article also presents the results of research on the TanyaAja application using the Sprint method, with this design an application is expected to be created with the aim of finding accurate and reliable information easily and quickly through online consultation with experts.